La ficción retrospectiva de la serie Juego de Tronos. Una mirada antropológica. - Fabela Reyes, Carla (2024)
An anthropological approach to the television series Game of Thrones is offered, using the notion of fiction. It is argued that this series is a fictional production of the past ande five of its characters are analyzed, seen as idealizing fictions. The different anchors of meaning offered by these characters are identified and they are located as imaginaries (cultural codingof represetations) of the Middle Ages. It is suggested that the latter have agency, because they activate or inhibit ways of relating to it. Augé's "triangle of the iaginary" is used to address the field in which the anthropological gaze can delve. It is possible the latter can speak about us, because it is a product of this society.